The relative effectiveness of teachers and learning software: Evidence from a field experiment in El Salvador - Konstantin Büchel; Martina Jakob; Christoph Kühnhanss; Daniel Steffen; Aymo Brunetti (University of Bern, Department of Economics, 2020)
This study provides novel evidence on the relative effectiveness of computer-assisted learning (CAL) software and traditional teaching. Based on a randomized controlled trial in Salvadoran primary schools, we evaluate three interventions that aim to improve learning outcomes in mathematics: (i) teacher-led classes, (ii) CAL classes monitored by a technical supervisor, and (iii) CAL classes instructed by a teacher. As all three interventions involve the same amount of additional mathematics lessons, we can directly compare the productivity of the three teaching methods. CAL lessons lead to larger improvements in students' mathematics skills than traditional teacher-centered classes. In addition, teachers add little to the effectiveness of learning software. Overall, our results highlight the value of CAL approaches in an environment with poorly qualified teachers.
Keywords: C93; I21; J24; O15; 330; computer-assisted learning; productivity in education; primary education; teacher content knowledge